The tradition-historical setting of Psalm 25: How wisdom motives contribute to its understanding - Human, Dirk J. (Verbum et ecclesia, 1996)
Psalm 25 is an acrostic psalm and an individual lament. Several tradition-historical motives and allusions can be identified in this text. Especially a few motives and images from the Old Testament wisdom literature contribute to the significance of the psalm. These motives are being identified and their function being determined in the context of the psalm as a whole. They are interwoven with other identified traditions and motives to contribute to the psalm’s understanding.